Droplet-in-oil array for picoliter-scale analysis based on sequential inkjet printing1. Issue 11 (7th June 2015) - Sun, Yingnan; Chen, Xiaodong; Zhou, Xiaoguang; Zhu, Jinbiao; Yu, Yude
<x xml:space="preserve">Abstract</x> We introduce a new model to describe the multiple printing procedure implemented by the inkjet printing approach. This non-contact and sequential picoliter droplet printing technology is named as sequential inkjet printing.